2019
DOI: 10.1186/s12911-019-0847-3
|View full text |Cite
|
Sign up to set email alerts
|

User evaluation of a novel SMS-based reminder system for supporting post-stroke rehabilitation

Abstract: Background According to WHO stroke is a growing societal challenge and the third leading cause of global disease-burden estimated using disability-adjusted life years. Rehabilitation after stroke is an area of mutual interest for health care in many countries. Within the health care sector there is a growing emphasis on ICT services to provide clients with easier access to information, self-evaluation, and self-management. ICT-supported care programs possible to use in clients’ home environments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The findings show that the participants set their goals based on activities they needed and/or wanted to perform in their everyday lives. This is in line with the results of the F@ce study in Uganda in which all participants were positive about the reminder system and felt that it helped them regain their abilities and that the follow-up system was beneficial to their rehabilitation process [ 16 ]. According to the national stroke guidelines [ 31 ] and rehabilitation research, setting goals is an essential part of the rehabilitation process [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings show that the participants set their goals based on activities they needed and/or wanted to perform in their everyday lives. This is in line with the results of the F@ce study in Uganda in which all participants were positive about the reminder system and felt that it helped them regain their abilities and that the follow-up system was beneficial to their rehabilitation process [ 16 ]. According to the national stroke guidelines [ 31 ] and rehabilitation research, setting goals is an essential part of the rehabilitation process [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the use of ICT-based interventions could reduce the number of home visits, thereby saving time and travel costs, particularly in rural areas [ 12 , 13 ]. ICT solutions have also shown to enable person-centred care [ 14 , 15 ] and facilitate communication and feedback from healthcare professionals [ 3 , 16 ]. A concern among people with stroke is their potentially limited ability to manage different ICT devices.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that RemindMe and the weekly conversations for two months, based on patients' needs, were appropriate to support the use of reminders for everyday tasks since it gave a structured way to evaluate the rehabilitation interventions. A similar result was pointed out in a study using SMS reminders and weekly phone calls to evaluate progress in the rehabilitation of stroke patients [31]. Interventions spread out over a longer time period give patients time to practice and thus become more independent [29].…”
Section: Discussionsupporting
confidence: 71%
“…Figure 1 outlines 5-stages of this review, including a summary of the number of articles identified from the initial database search and hand-searching ( n = 54, Step 3) through the final number of articles included in the review ( n = 12) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%